STRESS AND COPING STRATEGIES AMONG PARENTS OF CHILDREN WITH AUTISM SPECTRUM DISORDER - Mostafa, Mona H (PEOPLE: International Journal of Social Sciences, 2019)
Having a child with autism is a major event that negatively affects families, and force families to re-evaluate its plans, goals, and relationships in light of restrictions and limitations associated with child's disability, and resultant stresses in parents and their efficiency in coping with these stresses. This study aimed to assess stress and coping strategies among parents of children with autistic disorder. A purposive sample of thirty Parents of Autistic Children was recruited from the Center for Social and Preventive Medicine (child psychiatry out-patient clinic) in Abou-El-Rish University Hospital. Three tools were used to conduct the current study, demographic and medical data sheet, parent stress scale and coping strategies scale. The results indicated that, sixty percent of the studied parents had moderate level of stress. The results also showed that, more than fifty percent were using seeking information, avoidance and denial coping strategies. And finally, the results indicated high positive and significant correlation and acceptable predictable relation between levels of stress and coping strategies. In conclusion, children with autism require lifelong provision, management and service coordination.